2022
DOI: 10.1007/s00520-022-06836-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral chronic GVHD after allogeneic stem cell transplantation without total body irradiation performed at a young age

Abstract: Purpose Long-term survivors (LTSs) of allogeneic hematopoietic stem cell transplantation (allo-HCT) may experience oral long-term effects like chronic graft-versus-host disease (oral cGVHD). The aim of this study was to investigate oral cGVHD in patients treated at a young age (< 30 years) more than 5 years after allo-HCT without total body irradiation (TBI). Methods All 94 participants went through a semi-structured interview, and an oral examination.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Previous studies on oral manifestations in paediatric allogeneic bone marrow transplant recipients. Previous have reported on oral complications in patients following allogeneic HSCT (Bhatt et al, 2022;Bollero et al, 2018;Sholkamy et al, 2022;Tanem et al, 2022;Vignon et al, 2017), though the oral health in paediatric HSCT survivors has rarely been described (Chow et al, 2016;Effinger et al, 2014;Nicolatou-Galitis et al, 2001;Treister et al, 2005). Boer et al showed that oral mucosal cGVHD was the most common finding post-allogeneic HSCT (n = 35; 55.7%) in their cohort of patients, followed by xerostomia and pain (n = 34; 98.7%), mouth pain (n = 18; 29.5%) and difficulty in swallowing (n = 8; 13.1%), respectively (Boer et al, 2010).…”
Section: Ta B L Ementioning
confidence: 99%
“…Previous studies on oral manifestations in paediatric allogeneic bone marrow transplant recipients. Previous have reported on oral complications in patients following allogeneic HSCT (Bhatt et al, 2022;Bollero et al, 2018;Sholkamy et al, 2022;Tanem et al, 2022;Vignon et al, 2017), though the oral health in paediatric HSCT survivors has rarely been described (Chow et al, 2016;Effinger et al, 2014;Nicolatou-Galitis et al, 2001;Treister et al, 2005). Boer et al showed that oral mucosal cGVHD was the most common finding post-allogeneic HSCT (n = 35; 55.7%) in their cohort of patients, followed by xerostomia and pain (n = 34; 98.7%), mouth pain (n = 18; 29.5%) and difficulty in swallowing (n = 8; 13.1%), respectively (Boer et al, 2010).…”
Section: Ta B L Ementioning
confidence: 99%